Traduire Flaubert : Madame Bovary en version roumaine - Florica Courriol (Flaubert: Revue Critique et Génétique)
I intend to address in this paper the concrete problems I encountered when translating into Romanian FLAUBERT’s major work, Madame Bovary. First of all, its nature of retranslation has to be specified, since an existing version, published in the 1970s by a Romanian poet (Demostene Botez), was in fact in circulation when I started working on the original text. This previous translation was probably the result of a collective operation, as the split rhythm suggests at several points. In the meantime, other publishers saw fit to print additional versions in great haste. However, a mere examination of the problematic passages is sufficient enough to realize that the authors of the new versions only limited themselves to take up the first one. They improved the text here and there, “updated” some expressions, while keeping the glaring errors of Botez’s version.